(untitled) (ҚазҰУ Хабаршысы. Биология сериясы, 2015)
Исследована кинетика ферментативного гидролиза инулина, выделенного из топинамбура сорта Файз барака. Изучена ферментативная гидролизуемость инулина дрожжевой инвертазой. Выявлено, что инулин гидролизируется инвертазой при рН 4,0, температуре 30ºС и времени инкубации 1 час и исходной концентрации инулина -0,5-2,0%. Вышеуказанные результаты открывают возможности для получения функциональных соков и различных напитков, обогащенных фруктозанами. The kinetic characteristics of enzymatic hydrolysis of inulin isolated from topinambur Fays baraka was studied. The hydrolysis opportunity of unulin was investigated by application of yeast invertase. It was determined that unulin can be hydrolised by invertase at pH 4,0, 30ºС , during one hour, and initial inulin concentration of 0,5-2,0%. Above mentioned results open up the opportunity for the production of functional juices and various beverages enriched with fructozanes